Delineating the Relationship Between Insomnia, Dysfunctional Sleep Beliefs, Perceived Stress, Anxiety, and Depression - Lethbridge, Hannah P; Pidgeon, Aileen M (European Scientific Journal, ESJ, 2017)
Insomnia is a sleep disorder highly prevalent among university students which can increase the risk for developing anxiety and depression. Vulnerability to dysfunctional sleep beliefs, and cognitive arousal (perceived stress) have been shown to be predisposing factors for insomnia. Although insomnia in university students is associated with deleterious effects, limited research has focused on this at-risk population. The aim of the current study was to further delineate the relationships between insomnia, perceived stress, dysfunctional sleep beliefs, anxiety and depression among a sample of 195 Australian university students (33 males; 162 females; Mage = 22.37, SD = 7.02). Mediation and regression analyses were conducted to test findings. Results suggested the prevalence of insomnia among Australian university students was 16.9% respectively. Regression analyses indicated that anxiety, depression and insomnia all predicted outcomes in each other, indicative of a bidirectional relationship between these variables. Dysfunctional sleep beliefs partially mediated the predictive relationships between perceived stress, anxiety, depression, and insomnia. These findings may have implications for incorporating belief-targeted insomnia treatment into cognitive behavioural therapy for anxiety and depressive disorders.